2017
DOI: 10.1016/j.imr.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in biochemical parameters in the brain of transgenic Drosophila melanogaster model of Parkinson’s disease exposed to apigenin

Abstract: BackgroundOxidative stress is one of the key components of the pathology of various neurodegenerative disorders. Parkinson’s disease (PD) is characterized by the progressive loss of dopaminergic neurons owing to the aggregation of alpha-synuclein (αS) in the brain. A number of polyphenols have been reported to inhibit the αS aggregation resulting in the possible prevention of PD. The involvement of free radicals in mediating the neuronal death in PD has also been implicated.MethodsIn the present study, the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…It is often used in humans for Alzheimer's disease treatments. Flies that were reared on apigenin in their diet showed an increase in lifespan, glutathione, and dopamine content, as well as reduced oxidative stress and apoptosis in a transgenic Drosophila model of Parkinson's disease (Siddique and Jyoti, 2017). Treatment with caffeic acid alleviates oxidative stress induced neurotoxicity in cells and Drosophila models (Wu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It is often used in humans for Alzheimer's disease treatments. Flies that were reared on apigenin in their diet showed an increase in lifespan, glutathione, and dopamine content, as well as reduced oxidative stress and apoptosis in a transgenic Drosophila model of Parkinson's disease (Siddique and Jyoti, 2017). Treatment with caffeic acid alleviates oxidative stress induced neurotoxicity in cells and Drosophila models (Wu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…the progressive loss of dopaminergic neurons [34]. Various epidemiological and biochemical studies have recently identified promising compounds that may elicit neuroprotection in PD [24,28,29]. Due to ethical reasons the experiments cannot be performed directly on human, hence model organisms such as mice, fruit flies and worms have been developed in order to understand the biology of the disease as well as pharmacological interventions [18].…”
Section: Introductionmentioning
confidence: 99%
“…Reduced life span of fly has been linked with various neurodegenerative disorders [33]. Earlier studies on natural plant products/extract have also shown an increase in the life span of fruit flies expressing the symptoms of neurodegenerative disorder [15, 23, 33, 34, 35]. The exposure of PD flies to MB also prevents the loss in the activity of flies as is evident from the average activity pattern recorded by Drosophila Activity Monitor (DAM).…”
Section: Discussionmentioning
confidence: 99%